Efektivitas Perlindungan Hukum Konsumen dalam Kasus Malpraktik Medis pada Jasa Pelayanan Kesehatan di Indonesia - Ahmad Ryansyah1; Halimah Zahra; Berdhy Ursila Djamil; Muhammad Irfan Fauzan (Teewan Journal Solutions, 2025)
This study discusses the effectiveness of legal protection for patients as consumers of health services in cases of medical malpractice in Indonesia. Although various regulations such as the Health Law, the Medical Practice Law, and the Consumer Protection Law have been available, their implementation in the field still faces many obstacles, such as difficulties in providing evidence, inequality of position between patients and medical personnel, and minimal access to legal assistance. The case study of Ciputat Hospital shows indications of violations of patient rights. This study uses a literature study method with a juridical-sociological approach and an analysis of ethics and social responsibility based on the Crane and Matten framework. The results of the study emphasize the need for comprehensive reform of the law enforcement system, increased transparency of professional institutions, and legal education for the public to ensure fairer and more effective legal protection for patients who are victims of medical malpractice.